Environmental conditions shape the nature of a minimal bacterial genome - Magdalena Antczak (Nature Portfolio, 2019)
Minimal bacterial genomes still contain hundreds of genes of unknown function. Here the authors use in silico annotation methods and identify the environmental factors shaping a minimal genome.